Preliminary study on bird community assemblage and feeding guild in forest and developed areas of Muallim, Perak, Peninsular Malaysia - Salleh Hudin, Noraine; Bachu, Hasimah; Hairuman, Ahmad Humaidi; Ferdiana, Suci; Gebremichael, Gelaye (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
We investigated bird species richness and feeding guilds in two contrasting habitat types i.e. forest and developed areas in Muallim district of Perak, Peninsular Malaysia. Field surveys were conducted by using point-count observation along transects and mist-netting methods to determine the presence of bird species in the forest and developed areas. There were 28 species of birds from 23 families found in these habitats, where 13 species were found in forest and 15 species in the developed areas. The species richness was similar between forest and urbanized habitats. Forest birds were mainly frugivores and frugivore-insectivores whereas those from developed areas were insectivore-granivores and insectivores. Insects are important food resources in both habitats. Our results suggest that the availability of food resources in a locality may partly influence the community structure of Avifauna where conversion of forest into developed areas may induce shifts in the distribution of feeding guilds and the presence of species within the area. While developed areas have the capacity to support bird community, species that are specialized to forests may still be affected by the habitat change. Our study provides preliminary ideas on how bird communities in the tropical region are being shaped in response to urbanization. Further studies should cover a wider geographical range and over a longer period of surveys to yield a better understanding on this issue.